SOX: search for short baseline neutrino oscillations with Borexino. Issue 6 (May 2016) - Vivier, M; Agostini, M; Altenmüller, K; Appel, S; Bellini, G; Benziger, J; Berton, N; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; Calaprice, F; et al.
Abstract: The Borexino detector has convincingly shown its outstanding performances in the low energy regime through its accomplishments in the observation and study of the solar and geo neutrinos. It is then an ideal tool to perform a state of the art source-based experiment for testing the longstanding hypothesis of a fourth sterile neutrino with eV 2 mass, as suggested by several anomalies accumulated over the past three decades in source, reactor, and accelerator-based experiments. The SOX project aims at successively deploying two intense radioactive sources, made of Cerium (antineutrino) and Chromium (neutrino), respectively, in a dedicated pit located beneath the detector. The existence of such an eV 2 sterile neutrino would then show up as an unambiguous spatial and energy distortion in the count rate of neutrinos interacting within the active detector volume. This article reports on the latest developments about the first phase of the SOX experiment, namely CeSOX, and gives a realistic projection of CeSOX sensitivity to light sterile neutrinos in a simple (3+1) model.